Treatment of experimentally induced bovine respiratory disease in young calves with a single administration of a combination of florfenicol and meloxicam. (3rd November 2018) - Achard, Damien; Caruso‐Vares, Agathe; Collin, Jean‐François; McKelvie, Joanne; Reddick, David; Ramage, Cliff
Abstract : This study was designed to evaluate the efficacy of a new florfenicol/meloxicam combination (FMC) in calves with bovine respiratory disease. A total of 90 young calves were challenged via intratracheal deposition of 10 8 colony‐forming units of Mannheimia haemolytica . Data for 84 calves demonstrating a rectal temperature (RT) above 39.5°C and a combined total clinical score (TCS) greater than or equal to 3 were included. Calves were then randomly allocated to one of the three study groups (FMC; florfenicol/flunixin combination (FFC); or saline) and promptly treated. RT and TCS of calves treated with an FMC or FFC were consistently lower than RT and TCS of calves belonging to the control group (P<0.001). Moreover, at the end of the study, a high clinical cure rate was observed in calves treated with FMC (100 per cent) or FFC (96.6 per cent) whereas cure was limited for calves receiving saline (29.6 per cent). Interestingly, calves treated with FMC were cured without relapse more rapidly compared with calves treated with FFC (HR=1.76, P<0.05) and with a lower percentage of clinical relapse due to fever (P=0.05). These results underline the high efficacy of the FMC and are in line with the pharmacokinetic properties of florfenicol and meloxicam.